Regulation of TRIM24 by miR-511 modulates cell proliferation in gastric cancer. Issue 1 (December 2017) - Fang, Ziling; Zhang, Ling; Liao, Quan; Wang, Yi; Yu, Feng; Feng, Miao; Xiang, Xiaojun; Xiong, Jianping
Abstract Background Increasing evidence highlights the important roles of tripartite motif containing 24 (TRIM24) in tumor initiation and malignant progression in many tumors, including gastric cancer (GC). Although TRIM24 expression is remarkably upregulated during GC carcinogenesis, the molecular mechanisms underlying TRIM24 dysregulation remain unexplored. Methods In this study, miRNA target prediction tools were applied to explore miRNAs that potentially target TRIM24. Western blot and quantitative reverse-transcriptase PCR (qRT-PCR) were performed to detected TRIM24 and miR-511 expression in GC tissues and cell lines. Dual-luciferase reporter assay was utilized to validate if TRIM24 is a direct target gene of miR-511. CCK-8 assay, cell colony formation assay, EdU incorporation assay and cell cycle analysis were performed to determine whether miR-511-mediated regulation of TRIM24 could affect GC progression. Results In our study, miR-511 was found to be downregulated in GC and an inverse correlation was observed between TRIM24 and miR-511 expression in primary GC tissues and cell lines. Dual-luciferase reporter assay further verified TRIM24 is a direct target of miR-511. Functional assays showed miR-511 overexpression inhibited cell growth, colony formation ability and cell cycle progression. Conversely, inhibition of endogenous miR-511 promoted these phenotypes in GC cells. Moreover, reintroduction of TRIM24 rescued miR-511-induced inhibitory effects on GC cells. Furthermore, miR-511 elicits tumor-suppressive effects through inactivating PI3K/AKT and Wnt/β-catenin pathways by suppressing TRIM24. Conclusions Our results provide the new evidence supporting the tumor-suppressive role of miR-511 in GC by suppressing TRIM24, suggesting that this novel miR-511/TRIM24 axis is critical in the control of gastric cancer tumorigenesis.